Analisis Kompetensi Pedagogik Guru Madrasah Ibtidaiyah dalam Pembelajaran Daring pada Masa Pandemi Covid-19 - Lia Nur Atiqoh Bela Dina; Ika Ratih Sulistiani; Rufi'at Rufi'at (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This research aims to analyze the pedagogical competence of MI teachers in online learning during the covid-19 pandemic. This research is quantitative descriptive research. The population of this study is MI teachers in the Plumpang District of Tuban Regency. The sample was selected with a purposive sampling technique of 60 teachers. The data collection technique used surveys. The instrument used is a questionnaire. The questionnaire is distributed online through a google form. To obtain valid and reliable data, the device was previously tested for validity and reliability. Based on the research results, the pedagogical competence of MI teachers in the Plumpang subdistrict of Tuban district is in the category of good. The percentage of the average pedagogical competence of teachers in (1) indicators understand learners in depth by 74.2% with good categories, (2) indicators design learning, including understanding the educational foundation for the benefit of learning by 90.4% with excellent categories, (3) indicators carrying out learning by 85.4% with excellent categories, and (4) indicators carrying out learning evaluations by 72% with good categories. The pedagogical competence of teachers is said to be good if supported by being able to carry out the required indicators and can develop the competencies they have.